2014
DOI: 10.1039/c4cy00424h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yttria in Pt/TiO2 on sulfur resistance diesel oxidation catalysts: enhancement of low-temperature activity and stability

Abstract: Yttria in Pt/TiO2 catalyst improved the Pt dispersion and stabilized the structure, and hence enhanced the low-temperature activity and stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 74 publications
0
31
0
Order By: Relevance
“…It was confirmed by HRTEM (Fig. 36,37 In the process of Pt/FeO x -100 preparation, with the assistance of Pt nanoparticle, a small portion of Fe 3+ in the FeO x -100 was reduced to Fe 2+ forming a certain amount of Fe 3 O 4 phase (see in XRD patterns, Figure 6). They nearly preserve the particle size of Pt colloid nanoparticles.…”
Section: Role Of Feo X Microstructure In the Formation Of Pt-support mentioning
confidence: 70%
See 1 more Smart Citation
“…It was confirmed by HRTEM (Fig. 36,37 In the process of Pt/FeO x -100 preparation, with the assistance of Pt nanoparticle, a small portion of Fe 3+ in the FeO x -100 was reduced to Fe 2+ forming a certain amount of Fe 3 O 4 phase (see in XRD patterns, Figure 6). They nearly preserve the particle size of Pt colloid nanoparticles.…”
Section: Role Of Feo X Microstructure In the Formation Of Pt-support mentioning
confidence: 70%
“…34 As for Pt/FeO x -430 and Pt/FeO x -500, only α-Fe 2 O 3 phase can be observed, indicating the interface reaction is very weak in these two samples. 19,35,36 The molar ratio of Pt 2+ /Pt 0 is 0.74, 1.54 and 1.64 for Pt/FeO x -100, Pt/FeO x -300 and Pt/FeO x -500, indicating that the amount of Pt 2+ increases from Pt/FeO x -100 to Pt/FeO x -500. It was confirmed by HRTEM (Fig.…”
Section: Role Of Feo X Microstructure In the Formation Of Pt-support mentioning
confidence: 96%
“…Furthermore, the pore volume of Pt/WZ800 x decreased while the average pore diameter increased. It indicated that there are pores reconstructed during the process of calcining, which may lead to the encapsulation of the active site Pt [31]. So, it is not surprising that the gas yields over Cat7-Cat12 are much smaller than that of bare tubes even at high temperatures.…”
Section: The Catalytic Performance Of Catalystsmentioning
confidence: 94%
“…Besides for improving the contact condition, people also do a lot of work on enhancing the intrinsic activity of catalysts. Many catalysts, which including noble metals, perovskite‐type oxides, CeO 2 ‐based oxides, MnOx‐based oxides etc, have been designed and studied for soot combustion . In the past decades, owing to changing valence states of Mn 4+ , Mn 3+ and Mn 2+ in the MnO x , manganese oxides exhibit excellent catalytic performance for redox reactions.…”
Section: Introductionmentioning
confidence: 75%